Analisis Respon Mahasiswa Terhadap Semester Online Pada Mata Kuliah Fisika Dasar - Alpiana Hidayatulloh; Muh. Iman Darmawan; Hardani Hardani (Universitas Hamzanwadi, 2021)
This study aims to determine student responses to the implementation of online semesters in basic physics courses. The subjects of this study were first semester students as many as 28 students. The instrument used is a questionnaire of 5 statements answered via google form. Then the answers to the questionnaire were analyzed using a qualitative description, the data of which was written in a table. Based on the results of data analysis, the percentage of student responses to the online basic physics course semester is 83%. Based on the percentage, this shows that students give a positive response to the semester of basic physics courses.